Experimental evidence of MAP kinase gene expression on the response of intestinal anti-inflammatory drugs - Quaglio, Ana Elisa Valencise [UNESP]; Castilho, Anthony Cesar Souza [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Elsevier B. V., 2015)
The etiopathogenesis of inflammatory bowel disease (IBD) is unclear and further understanding of the mechanisms that regulate intestinal barrier integrity and function could give insight into its pathophysiology and mode of action of current drugs used to treat human IBD. Therefore, we investigated how intestinal inflammation affects Map kinase gene expression in rats, and if current intestinal anti-inflammatory drugs (sulphasalazine, prednisolone and azathioprine) act on these expressions. Macroscopic parameters of lesion, biochemical markers (myeloperoxidase, alkaline phosphatase and glutathione), gene expression of 13Map kinases, and histologic evaluations (optic, electronic scanning and transmission microscopy) were performed in rats with colonic inflammation induced by trinitrobenzenesulphonic (TNBS) acid. The colonic inflammation was characterized by a significant increase in the expression of Mapk1, Mapk3 and Mapk9 accompanied by a significant reduction in the expression ofMapk6. Alterations inMapk expression induced by TNBS were differentially counteracted after treatment with sulphasalazine, prednisolone and azathioprine. Protective effects were also related to the significant reduction of oxidative stress, which was related to increase Mapk1/3 expressions, which were reduced after pharmacological treatment. Mapk1, Mapk3,Mapk6 and Mapk9 gene expressionswere affected by colonic inflammation induced by TNBS in rats and counteracted by sulphasalazine, prednisolone and azathioprine treatments, suggesting that these genes participate in the pharmacological response produced for these drugs.
Keywords: Inflammatory bowel disease; Intestinal anti-inflammatory drugs; Intestinal inflammation; Map kinases